Improving the nutritional value of canola seed by gamma irradiation - Mervat M. Anwar; Safaa E. Ali; Essam H. Nasr (Journal of Radiation Research and Applied Sciences, 2015)
This investigation aims to evaluate the effects of γ-irradiation on anti-nutritional factors, in-vitro protein digestibility and functional properties of canola meal protein, physicochemical properties and fatty acid composition of canola seed oil. Irradiation at doses 10, 20, 30 KGy had no effects on the chemical composition of canola seed, while decreased the total glucosinolate content by 15.6, 30.4 and 49.4%; and phytic acid by 29, 55 and 100%, respectively. On contrary, in-vitro protein digestibility increased to 59.1, 61.4 and 71.8% by the same doses, respectively. Water absorption and fat absorption increased by increasing irradiation doses, whilst decreased foaming capacity. Refractive index was between 1.4636 and 1.4687, acid value between 0.72 and 1.10%, peroxide value between 3.40 and 7.36 meq/kg oil. Iodine number and saponification value were 122 and 175 at dose 30 KGy, respectively. Oxidative stability decreased to 17.8, 16.4 and 14.9 h by doses 10, 20 and 30 KGy, respectively, compared to control (18.9 h). The contents of oleic and linoleinic acid were ranged between 60.44–61.69% and 21.72–22.09% respectively. So, γ-irradiation considered a safe method which reduced the anti-nutritional factors and improve both nutritional value and functional properties of canola seed.